The Effectiveness of Peer Tutoring Strategy toward Students’ Reading Comprehension of Descriptive Text - Henah Nadia; Siti Suharsih; Ika Handayani (Journal of English Language Teaching and Cultural Studies, 2023)
The goal of this research is to obtain empirical data about the effectiveness of peer tutoring strategy toward students' reading comprehension. To achieve that goal, this research used a quasi-experimental design involving tenth grade students of SMA Al-Mubarok Serang. The population used was 110 students. The sample consists of 20 students from experimental class and 20 students’ of control class which are selected using cluster random sampling. The results of the post-test revealed that the experimental class was a significantly higher score than the control class. In addition, the results of the Independent Sample T-Test revealed that the value was 0.29, while the alpha (a) was 0.05, which was 0.29<0.05. This is also supported by the results of the effect size test which has a value 2.75 and the category was strong effect (significant). Therefore, it was proven that the use of peer tutoring strategy was effective toward students’ reading comprehension of descriptive text at tenth grade of SMA Al-Mubarok. Thus, the use of peer tutoring strategy is suggested toward students’ reading comprehension of descriptive text.